(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The rapid development of artificial intelligence technologies is significantly affecting all spheres of modern society, particularly in the processes of information production, analysis, and dissemination. This article comprehensively analyzes the role, opportunities, and potential risks of artificial intelligence not only in journalism but also in education, economics, medicine, and management sectors.